ORGANIZING SELF-EDUCATION ACTIVITIES FOR MEDICAL COLLEGE STUDENTS IN THE CONTEXT OF BLENDED LEARNING - Pysmenna Oleksandra (Alfred Nobel University Publisher, 2024)
The article aims to review current trends in the organization of self-education activities for medical college students, models of blended learning, and its main components that ensure the self-education of future nursing specialists. The research methods are terminological and comparative analysis, generalization, specification, and modelling. Based on the analysis of primary sources, it has been established that self-education activities are a type of educational and cognitive activity motivated by an internal drive for self-improvement and facilitated by the use of specific methods for seeking and assimilating social experience. It has been emphasized that through self-education, medical professionals are better able to handle complex clinical cases and provide high-quality medical care to their patients, including via the use of digital technologies. Blended learning is defined as a combination of traditional face-to-face (contact) learning and computer-mediated or online learning. It has been pointed out that the implementation of blended learning requires the development of appropriate pedagogical design and innovations that ensure the application of adequate teaching and assessment methods with carefully planned content and structured academic courses. The blended learning system is presented as an integration of face-to-face classroom and clinical sessions, independent student work, and online learning. It has been noted that in blended models, the supply of educational material and interaction with the teacher can occur in both physical and virtual environments, during both classroom sessions and asynchronously during extracurricular activities. The specifics of self-education activities for medical college students using some models such as rotational, laboratory, independent blended learning, flexible learning, enriched virtual learning, flipped classroom, and personalized learning have been described. In each model, the core element is identified as the electronic educational resource. In the blended learning system such a resource is viewed not as an auxiliary tool of the traditional educational process but as the one that successfully combines traditional and distance learning forms, incorporating both non-digital and digital technologies. It has been determined that blended learning is based on the flexible combination of in-class learning (contact hours) with online sessions (asynchronously or synchronously). Among the tools for blended learning used in organizing self-education activities for medical college students, the following have been highlighted and described: online lectures, practical sessions in webinar mode, project and group work online, learning management systems such as LMS Moodle, laboratory work in a blended format, virtual and augmented reality technologies, a combination of formal and nonformal education, self-testing complexes, webinar consultations, artificial intelligence technologies, and specialized medical applications. It has been concluded regarding the feasibility of implementing blended learning in the training of medical college students and the organization of their self-education activities. This will enhance the quality of education, and the efficiency of resource utilization of educational institutions, increase the level of professional expertise and mobility of teachers, and ultimately provide additional competitive advantages to the educational institution in the educational services market.